2019
DOI: 10.1038/s41929-019-0378-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct catalytic transformation of white phosphorus into arylphosphines and phosphonium salts

Abstract: Phosphorus compounds are ubiquitous in the chemical sciences, finding applications throughout industry and academia. Of particular interest to synthetic chemists are organophosphorus compounds, which contain P-C bonds. However, state-of-the-art processes for the synthesis of these important materials rely on an inefficient, stepwise methodology involving initial oxidation of white phosphorus (P 4 ) with hazardous chlorine gas and the subsequent displacement of chloride ions. Catalytic P 4 organofunctionalisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 35 publications
3
58
0
1
Order By: Relevance
“…Phosphorus is one of the essential biogenic elements required by every living organism, 94 and phosphorus compounds play a significant role in the industry, including ligands design, organic synthesis, drugs, optoelectronic materials and fertilisers etc., due to their diverse array of useful chemical, physical and biological properties. 95 However, these phosphoruscontaining species are currently prepared via hazardous and wasteful multi-step procedures involving the initial transformation of P 4 to PCl 3 and PCl 5 .…”
Section: Degradation Of P 4 and Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus is one of the essential biogenic elements required by every living organism, 94 and phosphorus compounds play a significant role in the industry, including ligands design, organic synthesis, drugs, optoelectronic materials and fertilisers etc., due to their diverse array of useful chemical, physical and biological properties. 95 However, these phosphoruscontaining species are currently prepared via hazardous and wasteful multi-step procedures involving the initial transformation of P 4 to PCl 3 and PCl 5 .…”
Section: Degradation Of P 4 and Asmentioning
confidence: 99%
“…95 However, these phosphoruscontaining species are currently prepared via hazardous and wasteful multi-step procedures involving the initial transformation of P 4 to PCl 3 and PCl 5 . 94 Though degradation of P 4 has been established by transition-metal systems, 96 highly reactive main-group compounds also show reactivity towards P 4 , for example, cyclic alkyl amino carbenes and N-heterocyclic carbenes undergo a nucleophilic attack at P 4 to give degradation products, low-valent aluminium and gallium compounds were also found to cleave P-P bonds. 16b Silylene-mediated degradation procedures show excellent prospects due to their inherent advantages including mild conditions and easier purification processes.…”
Section: Degradation Of P 4 and Asmentioning
confidence: 99%
“…[17] We recently demonstrated the visible light-driven, iridium-catalyzed direct functionalization of white phosphorus, which gives triarylphosphines and tetraarylphosphonium salts under mild reaction conditions. [18] It was found that this method arylates P 4 in as tepwise manner,g iving rise to H 2 PAr, HPAr 2 , PAr 3 ,a nd PAr 4 + productsi naw ell-defineds equence. Buildingu pon these observations, herein we report that the same reaction protocol can be used to provide convenient accesst oasymmetrical tertiaryp hosphinesa nd quaternary phosphoniums alts, by starting from the commercially availablep rimary and secondary phosphines H 2 PPh and HPPh 2 .F urthermore, we show that the previously employed noblem etal photocatalyst can be replaced by the inexpensive organic photocatalyst 3DPA-FIPN, not only in these reactions but also in the direct arylation of P 4 .…”
Section: Introductionmentioning
confidence: 96%
“…[19] Our protocols hence provide simple and practical synthetic access to ab road range of symmetric and asymmetric target products (Figure 1, bottom box, Figure 2). Based upon our previouso bservations, [18] we reasoned that the commercially-available aryl phosphines HPPh 2 and H 2 PPh could be transformed into asymmetricalt ertiaryp hosphines (RPPh 2 or R 2 PPh) and quaternary phosphoniums alts (R 2 PPh 2 + or R 3 PPh + )t hrough reactionw ith aryl iodides, mediated by the same photocatalytic system previously used for the arylation of P 4 .T hus, as olutionc ontaining the photocatalyst [Ir(dtbbpy)(ppy) 2 ]PF 6 ([1]PF 6 ;d tbbpy = 4,4'-bis-tert-butyl-2,2'-bipyridine, ppy = 2-(2-pyridyl)phenyl;s tructure shown in Table 1), HPPh 2 ,t he electron donor Et 3 N, and am odel substrate 2-iodotoluene in aC H 3 CN/PhH mixture (3:1) was irradiated with blue LED light (l max = 455 nm) for 18 h. Gratifyingly,t his reaction was indeed found to yield 63 %o ft he desired tertiary phosphine product. Further investigations revealed that the yield could be further optimized to 71 %b ya djusting the ratios of Et 3 N, aryl iodide and catalyst [ 1]PF 6 (Table 1, I-3).…”
Section: Introductionmentioning
confidence: 97%
“…The eco‐friendly and atom efficient method of direct conversion of white phosphorus to phosphine containing products has also been considered . Currently, it was demonstrated that direct catalytic transformation of P 4 into organo‐phosphorus compounds using a transition metal complex is possible . However, the stoichiometric and catalytic reaction of white phosphorus under mild conditions is challenging for both transition metal and main group compounds.…”
Section: Small Molecule Activation With Acyclic Silylenesmentioning
confidence: 99%